2015
DOI: 10.1021/acs.est.5b00964
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of 1,4-Dioxane Attenuation at Groundwater Sites Contaminated with Chlorinated Solvents and 1,4-Dioxane

Abstract: There is a critical need to develop appropriate management strategies for 1,4-dioxane (dioxane) due to its widespread occurrence and perceived recalcitrance at groundwater sites where chlorinated solvents are present. A comprehensive evaluation of California state (GeoTracker) and Air Force monitoring records was used to provide significant evidence of dioxane attenuation at field sites. Temporal changes in the site-wide maximum concentrations were used to estimate source attenuation rates at the GeoTracker si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 28 publications
3
62
0
Order By: Relevance
“…To date, there are over 30 published papers that document 1,4‐dioxane biodegradation in environmental and laboratory studies, and biological degradation of this compound is widely recognized. Indeed, environmental studies focusing on natural in situ biodegradation of 1,4‐dioxane are on the rise (Adamson et al., ; Chiang et al., ; Lippincott et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are over 30 published papers that document 1,4‐dioxane biodegradation in environmental and laboratory studies, and biological degradation of this compound is widely recognized. Indeed, environmental studies focusing on natural in situ biodegradation of 1,4‐dioxane are on the rise (Adamson et al., ; Chiang et al., ; Lippincott et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Adamson et al. () report that attenuation of 1,4‐dioxane happens at a small yet significant number of project sites evaluated in California. This study also refers to Air Force databases in which some wells show an equivalent half‐life for 1,4‐dioxane of 2 to 5 years.…”
Section: Overview Of Sustainability Drivers By Technologymentioning
confidence: 99%
“…The natural attenuation research performed in the Adamson et al. () study discussed below revealed that 1,4‐dioxane was detected in 191 (32 percent) of the 589 California sites where it was part of the analytical suite. Presumably, the 1,4‐dioxane testing was related to other chlorinated solvent contamination and, therefore, this percentage may be biased higher than the total universe of contaminated sites; however, the results clearly demonstrate the prevalence of 1,4‐dioxane as a groundwater contaminant.…”
Section: Introductionmentioning
confidence: 99%